PENGARUH AKSES MODAL DAN AKSES PENDIDIKAN TERHADAP DISTRIBUSI PENDAPATAN DI SUMATERA BARAT - Diana Hutami Putri; Yulhendri Yulhendri (Universitas Negeri Padang, 2019)
This study was conducted to find out (1) the effect of capital access on income distribution, (2) the effect of education on income distribution. This research is descriptive and associative. In this study, the object of the research was the province of West Sumatra. The type of data used in this study is secondary data. The data used in this study is the ratio of Gini West Sumatra, access to capital (umkm and loans) and education (budget). The data collection technique used in this study is the retrieval of data from related institutions, namely the BPS of West Sumatra Province and the library used as support. The technique used to analyze data is multiple linear regression analysis. The prerequisite test is done by chow test, hausman test, and lm test. Based on this study, it was found that (1) capital access has a positive and significant influence on income distribution. (2) education has a positive and significant influence on income distribution.Keyword: Capital Access, Education, Distribution Incom